Processing of Sugarcane Bagasse (Saccharum officinarum L.) for Bioplastic Production with the Addition of Glycerol and Chitosan - Annisa Nurul Sakinah Lubis; Melfa Aisyah Hutasuhut; Leni Widiarti (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to analyze the effects of varying bagasse mass, as well as the roles of glycerol as a plasticizer and chitosan as a reinforcing agent, on the physical, mechanical, thermal, and morphological properties of bioplastics. The research was conducted through laboratory experiments using a completely randomized design (CRD). The mass of bagasse was varied at 2, 4, 6, 8, and 10 g, while the concentrations of glycerol and chitosan were kept constant across all treatments. The results showed that increasing the mass of bagasse tended to produce bioplastics with greater stiffness and brittleness, while also reducing surface homogeneity, as observed through SEM analysis. The addition of glycerol improved material flexibility, as indicated by an increase in elongation from 11.8% to 27.9%. Meanwhile, chitosan contributed to enhanced tensile strength, which increased from 0.4199 MPa to 1.4221 MPa. In addition, higher bagasse content improved thermal resistance, as demonstrated by DSC analysis. The highest biodegradation rate reached 73.95% in a sample with a specific composition during the testing period. FTIR analysis confirmed the presence of functional group interactions among cellulose, glycerol, and chitosan within the bioplastic matrix. These findings indicate that the combination of bagasse with glycerol and chitosan can produce bioplastics with a balanced combination of flexibility, mechanical strength, and biodegradability. This study contributes to the utilization of agricultural waste as a value-added raw material for bioplastic production and supports the development of sustainable, environmentally friendly materials.